Analisis Penyebab Lead Time Pemenuhan Pesanan dan Produksi Panjang PT X - Sandra Lukita; I Gede Agus Widyadana (Jurnal Titra, 2020)
This research was conducted to find out the cause of long lead time order fulfilment and production on PT X. Previous research conducted on the identification of key factors lead time of PT X order fulfilment with the DEMATEL method, found BOM problems namely incomplete BOM in terms of both quantity and compatibility resulting in less components so that production shutdown as one of the key factors causing the length of PT X lead time long. The BOM problem in this study is proven to be one of the factors causing lead time of PT X order fulfilment. BOM problem solving based on production balance can have a 5.3% impact the problem of production balance that causes PT X production lead time to be long. Supplier complaints in this study were also found to be another important factor that caused the lead time for PT X orders to be fulfilled. Solving supplier complaint problems based on production balance can have a 57.9% effect of solving the production balance problem which causes the PT X production lead time to be long.